POLITICS AND MYSTICISM - Jokubaitis, Alvydas (Politologija, 2015)
The article is based on an idea that there are four different modes of understanding reality – practice, science, art and mysticism. Political liberalism demands separation of public and private beliefs. However, mystical understanding of reality is not a system of propositions and beliefs. This is why one can speak of a conflict between liberalism and mystical understanding of reality. Political liberalism imposes a certain understanding of reality on believers. Liberals propose to remove religious convictions from public life and not to treat them as a basis of politics. They forget that mystics have the biggest trouble namely with convictions. To turn the reality of God into words for them is always the hardest task. Mystics find God before words, concepts and discourses. Liberals reduce religion to convictions and demand from mystics to comprehend that, which in their opinion is not comprehensible. There is a tension between liberalism and people who have mystical experiences. Liberals narrow down religious experience to convictions. However, mystical experience is a much broader subject. Behind it stands an understanding of world that has its own standards of reality.